الاتصال في العلاقات العامة .. الوسائل والجمهور - جفال, سامية (Sciences humaines; Vol. 33 (2014): SCIENCES HUMAINES, 2014)
العلاقات العامة هي الجهاز الذي يربط المؤسسة بجمهورها الداخلي والخارجي . وللتقدم التقني في وسائل ال إ علام المختلفة ولاسيما فيما يتعلق بالاتصال دور في زيادة فعالية هذا الجهاز. ازداد الطلب في الآونة الأخيرة على تطوير أقسام العلاقات العامة، وسبب الإقبال على هذا الفرع من فروع الإدارة هو الدور الذي يلعبه هذا الجهاز وأهميته لكل مؤسسة، حيث يقوم  ب نقل صورة للأنشطة والخدمات التي تقدمها للجمهور وحاجة الجمهور للحصول على تلك المعلومات .      Public Relations is the organ that connects its public institution of internal and external. And technical progress in various media, particularly with regard to communication role in increasing the effectiveness of this device. Increased demand in recent sections on the development of public relations, and the reason for the popularity of this branch of the Department is Alldoralve role of this device and importance of each institution where the transfer of a picture of the active and the services provided by the public and the public need for suchinformation